What are the determinants of interpersonal trust in dyadic negotiations? Meta-analytic evidence and implications for future research - LU, Serena Changhong (Institutional Knowledge at Singapore Management University, 2017)
Given the practical importance of interpersonal trust in dyadic negotiations, scholars have increasingly turned their attention to the study of determinants of trust in negotiations. However, research in this area has not been well connected or integrated, which limits the ability of scholars and practitioners to ascertain the state of current scientific knowledge and identify questions for future research. Based on attribution theory and social exchange theory, we present a conceptual framework for understanding how a variety of factors combine to influence the development of interpersonal trust in dyadic negotiations. Then, to verify the conceptual framework, we identified and meta-analysed findings from a total of 25 independent studies of determinants of trust in negotiations. The meta-analyses provided support for two of the three factors in the conceptual framework – trustor attributes and shared attributes – that are likely to influence an individual’s trust in a negotiation partner. The framework and findings provide valuable scientific insights on trust and negotiation, and also valuable practical insights for negotiation practitioners.